DEVELOPMENT OF DIGITAL TRANSFORMATION MODEL IN HAJJ AND UMRAH TRAVEL USING QUALITATIVE METHODS - Rossitika, Amanda Rizky; Mudjahidin, Mudjahidin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Digital transformation involves reshaping business operations through digital technologies, fostering flexibility and responsiveness to market demands. For Hajj and Umrah travel companies, adopting digital transformation can drive productivity, innovate value creation, and improve customer interactions. However, challenges arise due to limited consideration of leadership and consumer preferences, which are critical in directing and tailoring digital initiatives. Previous studies have focused predominantly on technological factors, often neglecting these human-centered elements crucial for competitiveness. This paper addresses this gap by developing a digital transformation model that emphasizes the roles of leadership and consumer preferences. Data were gathered through in-depth interviews, observations, and document analysis with key stakeholders and customers in selected Hajj and Umrah travel companies. By using a qualitative case study approach, the research explores how leadership and consumer insights shape digital strategies and business processes, ultimately enhancing competitiveness. The findings highlight the significant impact of leadership and consumer preferences on competitive advantage and introduce new indicators for implementing digital strategies effectively. This paper contributes to digital transformation theory by integrating leadership and consumer preference factors, offering Hajj and Umrah companies practical guidance for designing impactful digital strategies and fostering customer engagement